Dynamic soil-structure interaction models for fragility characterisation of buildings with shallow foundations. Issue 132 (May 2020) - Cavalieri, Francesco; Correia, António A.; Crowley, Helen; Pinho, Rui
Abstract: Dynamic Soil–Structure Interaction (SSI), involving the coupling of structure, foundation and soil, is a crucial and challenging problem, especially when soil nonlinearity plays an important role. This paper shows the impact of adopting different SSI models on the assessment of seismic fragility functions. The linear substructure approach is initially adopted by implementing two different models, the first of which is one-dimensional and includes, between the foundation node and the ground, a translational elastic spring and a dashpot, whose stiffness and viscous damping are retrieved from the real and imaginary parts of the dynamic impedance at the first natural frequency of the structure. The second and more refined model is a Lumped-Parameter Model (LPM) accounting for frequency dependence of the impedance. In order to explore the sensitivity of fragility functions to the linearity assumption, an additional approach, including soil nonlinearities, is employed. A nonlinear footing macro-element is adopted to model the near-field behaviour by condensing the entire soil-foundation system into a single nonlinear element at the base of the superstructure. Energy dissipation through radiation damping is also accounted for. The superstructure response is simulated in all approaches as a simple nonlinear single-degree-of-freedom (SDOF) system. The comparison between the adopted approaches is evaluated in terms of their effects on the characterisation of fragility functions for unreinforced masonry buildings (URM) on shallow foundations. Highlights: In response to induced seismicity in the Netherlands, fragility functions are needed Dynamic Soil–Structure Interaction (SSI) is a crucial and challenging problem Three SSI models are implemented and their effects on fragility functions are compared The collapse fragility curves for ten unreinforced masonry index buildings are provided The considered inelastic behaviour leads to energy dissipation and smaller displacements